The Effect of Autologous Protein Solution on the Inflammatory Cascade in Stimulated Equine Chondrocytes - Linardi, Renata L.; Dodson, Michael E.; Moss, Kaitlyn L.; King, William J.; Ortved, Kyla F. (Frontiers in Veterinary Science, 2019)
Cartilage injury occurs commonly in equine athletes, often precipitating posttraumatic osteoarthritis (PTOA). Orthobiologics such as autologous conditioned serum (ACS) and autologous protein solution (APS) may be useful in decreasing posttraumatic inflammation, thereby preventing PTOA. The objective of this study was to quantify cytokine concentrations in ACS and APS and evaluate the protective effects of ACS and APS on inflamed chondrocytes cultured in vitro. We hypothesized that the combination of platelet-derived growth factors and anti-inflammatory cytokines present in APS would be superior in decreasing the inflammatory and catabolic cascade in inflamed chondrocytes when compared to ACS in which platelets are excluded from the preparation. Chondrocytes were isolated from the cartilage of femoral trochlear ridges of 6 horses and cultured in 12-well transwell plates. Treatment groups included: 1) control 2) autologous protein solution (Pro-Stride; Owl Manor), and 3) autologous conditioned serum (IRAP II; Arthrex). Each group was unstimulated or stimulated with IL-1 and TNF- for 48 hours. The concentration of IL-1, IL-6, TNF-, MMP-3, MMP-13, and IL-10 was quantified using a fluorescent bead-based multiplex assay. IL-1Ra concentration was quantified using ELISA. APS and ACS both had significantly increased concentrations of IL-1Ra without a concurrent increase in IL-1 concentration. After 48 hours of culture, media from chondrocytes treated with APS contained significantly increased concentrations of IL-1Ra and IL-10. APS-treated cultures had increased concentrations of IL-6. Overall, APS effectively concentrated IL-1Ra without an incubation period and media from APS-treated chondrocytes had increased concentrations of chondroprotective (IL-1Ra and IL-10) and modulatory (IL-6) cytokines, which may be beneficial in the treatment of inflammatory conditions such as PTOA.